(untitled) (Revista de Ciências Agroveterinárias, 2024)
This experiment was conducted to investigate the growth performance, haematological and serum biochemistry indices of broilers fed diets containing Vitex doniana leaf meal (VDLM). A total of 120 unsexed broilers were allocated to four treatments of T1, T2, T3 and T4 and replicated three times with ten birds per replicate in a Completely Randomized Design. The birds in each treatment were fed with diets containing 0.0, 2.5, 5.0 and 7.5% VDLM respectively. Growth performances, packed cell volume, red blood cell count, haemoglobin, white blood cell count, lymphocytes, neutrophils, mean corpuscular volume, mean corpuscular haemoglobin concentration, platelet count, aspartate amino transaminase, alanine amino transaminase, alkaline phosphate, high density lipoprotein, low density lipoprotein, cholesterol, albumin, globulin, urea, glucose, total protein and creatinine were evaluated. Growth performance results showed that there were significant differences (P<0.05) in all the measured parameters except feed cost. The result of the experiment showed that there were significant differences (P<0.05) in all the heamatological and serum biochemistry parameters at starter and finisher phases, except for haemoglobin and mean corpuscular haemoglobin concentration which were not significantly different (P>0.05) at the starter phase. Growth performances of broilers fed control diets were better than the other treatment diets. Mean corpuscular haemoglobin, platelet count and low density lipoprotein decreased progressively while mean corpuscular volume, neutrophils, alanine amino transaminase, aspartate amino transaminase and creatinine increased progressively with increase in the inclusion of VDLM at the finisher phase. At the finisher phase, haemoglobin, packed cell volume and glucose decreased progressively while high density lipoprotein increased progressively with increase in VDLM. The results show that VDLM reduced the growth performance but improved the heamatological and serum biochemistry of broiler at lower levels of inclusion.